2003
DOI: 10.1046/j.1365-2842.2003.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the influence of removable partial denture and chemical control on the levels of Streptococcus mutans in saliva

Abstract: Some studies have evaluated the salivary levels of mutans streptococci (MS) in removable partial denture (RPD) users. Saliva samples (2.0 mL) were obtained from 31 patients in six periods: (T0): immediately before installation of RPD; (T8): 8 days after T0; (T48): 48 days after T0; (T92): 92 days after T0; (T140): 140 days after T0 and (T189): 189 days after T0. The samples were vortexed and serially diluted from 10(-1) to 10(-6) in 0.05 m phosphate buffer (pH 7.4). From each dilution, 0.025 mL was plated on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 30 publications
1
40
0
1
Order By: Relevance
“…However, there was a large between-individual variation in time of MS recolonization. Similar results were recorded by Rocha et al 39 With this variability in treatment response in mind, Wallman et al 42 devised individualized treatment plans for patients with an initial MS count > 5.0 Â 10 5 CFU/ml of saliva and a high number of restored teeth. Treatment effects were monitored for 12 weeks, with treatment repeated from 3 to 9 times in order to hold MS values below the originally detected levels.…”
Section: Chlorhexidine Gelsupporting
confidence: 57%
See 1 more Smart Citation
“…However, there was a large between-individual variation in time of MS recolonization. Similar results were recorded by Rocha et al 39 With this variability in treatment response in mind, Wallman et al 42 devised individualized treatment plans for patients with an initial MS count > 5.0 Â 10 5 CFU/ml of saliva and a high number of restored teeth. Treatment effects were monitored for 12 weeks, with treatment repeated from 3 to 9 times in order to hold MS values below the originally detected levels.…”
Section: Chlorhexidine Gelsupporting
confidence: 57%
“…32,33 CHX gel at 0.2%, 0.5%, and 1% is applied with a toothbrush, 30,31,34 while 1% and 5% gels are applied through professional prophylaxis 35 and with the aid of individual trays. [36][37][38][39] Toothbrush application of 0.2% and 0.5% CHX gel did not cause any significant decrease in MS levels as compared to a placebo gel. 30,31 Both studies showed a decrease in these microorganisms in both test and control group.…”
Section: Chlorhexidine Gelmentioning
confidence: 86%
“…47 In longitudinal studies, significantly elevated salivary counts of mutans streptococci were found between 4 and 6 months after insertion of RPDs compared with baseline. 48,49 Together, the above studies indicate that mutans streptococci benefit from the introduction of RPDs into the mouth. It is possible that these organisms proliferate on the denture materials themselves; alternatively, the presence of novel sheltered sites may be responsible for their increased growth.…”
Section: Mutans Streptococci and Lactobacillimentioning
confidence: 86%
“…Several factors can influence the re-colonization time of SM in individuals treated with chlorhexidine gel, including the number of restored tooth surfaces and retaining sites, as well as the amount of sucrose consumed daily by each volunteer [12,16,17]. In order to limit the effect of these factors on the re-colonization time of SM, restorative treatment of all children was made before the start of the experiment, and children and parents or guardians were advised to reduce sucrose consumption during the experiment period.…”
Section: Discussionmentioning
confidence: 99%
“…Sterile test tubes were used for saliva collection, containing ten glass beads to facilitate homogenization in tube shaker (Vortex). Before processing, the tubes were kept on crushed ice [16].…”
Section: Collection Of Saliva Samplesmentioning
confidence: 99%